Effect Of Removal Of Some Photosynthetic Organs On Yield Components In Durum Wheat (Triticum Aestivum L.) - Balkan, Alpay; Gençtan, Temel; Bilgin, Oguz (Bangladesh Journal of Agricultural Research, 2011)
This research was carried out in experimental field of Field Crops Department of Agricultural Faculty of Namik Kemal University in randomized split block design with three replications per treatment during 2004-2005 and 2005-2006. The objective of this study was to find out the contribution rates of awn, flag leaf, 1st upper leaf blade, 2nd upper leaf blade and other leaf blades to main yield components in three durum wheat cultivars (cv. Kiziltan-91, Kunduru-1149, and Yelken-2000). The results of this experiment showed that removal of awn, flag leaf, 1st upper leaf blade, 2nd upper leaf blade, and other leaf blades reduced significantly spike weight, number of grains per spike, grain weight per spike, and 1000-grain weight except the number of spikelets per spike. It was concluded that the organs play an important role in grain yield in durum wheat during grain filling stage. Keywords: Photosynthetic organs; yield components; durum wheat. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9224 BJAR 2011; 36(1): 1-12